L’eterno ritorno della crisi in America Latina - Tognonato, Claudio (SocietàMutamentoPolitica, 2018)
In order to analyze the Latin American situation, we can start in seventies, with the unilateral termination of the Bretton Woods Agreements. In response to economic and currency instability, the monetarism theory of the Milton Friedman gained credence. A decision was made to try them out first in Chile and after in Argentina. The decline of human, civil, political, economic and cultural rights during the neoliberal period in Latin America ended with the 2001 crisis and the economic and political failure of Argentina. The withdrawal from the neoliberal model is a gradual process which is generating new regional political structures. It is no longer the markets that direct policies but governments. In the last years Latin America is marked by a return to the past. The crisis of democracies manifests itself in various coercive forms that are implemented against the will of the people, from economic coup, to media coups, to those implemented by sectors of the magistracy. It would seem that there’s no need to implement the classic coups d’état. Other instruments are put in place with a lower cost. The region is again a test bed? A laboratory in which to implement new democratic forms of exclusion?